1973
DOI: 10.1002/cpt1973144part1572
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of methotrexate

Abstract: The pharmacokinetics of SH‐methotrexate were studied in 22 patients with malignancies. Following the intravenous administration of 30 mg methotrexate (Mtx) per square meter, the plasma disappearance was triphasic with half‐lifes of 0.7.5 ± 0.11,3.49 ± 0 . .55, and 26.99 ± 4.44 hours, respectively. The urinary excretion of radioactivity paralleled the plasma data for most patients. A metabolite was found in urine that eluted before Mix when chromatographed on a diethylaminoethyl (DEAE) cellulose column. The exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
0
3

Year Published

1975
1975
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(33 citation statements)
references
References 7 publications
(8 reference statements)
1
29
0
3
Order By: Relevance
“…Quite marked interpatient variation in the rate of distribution after an i.v. dose was evident in this study, and was similar to that reported in adults (Huffman et al, 1973). This may have been due to differences in tissue-or serum protein-binding associated with very high drug concentrations.…”
supporting
confidence: 89%
“…Quite marked interpatient variation in the rate of distribution after an i.v. dose was evident in this study, and was similar to that reported in adults (Huffman et al, 1973). This may have been due to differences in tissue-or serum protein-binding associated with very high drug concentrations.…”
supporting
confidence: 89%
“…While the utility of routine pharmacokinetic monitoring is apparent, in practice the existing techniques for methotrexate assay have been complex, time consuming, and of limited availability. The other methods include a highly sensitive dihydrofolate reductase inhibition assay (9,11), radioimmunoassay (24), a less sensitive fluorometric method (9), and the use of radiolabeled drug (22,23). The present competitive binding procedure has sensitivity comparable to the enzymatic method, and is capable of determining levels below 5 X 10-9 M, the probable threshold for toxicity to normal tissue (25).…”
mentioning
confidence: 99%
“…In man, 4-amino-N10-methyl pteroic acid is found in the urine 24-96 h after the administration of MTX, in amounts up to 30%o of the total dose MTX given. It is, however, not detectable at all during the first 24 h (Huffman et al, 1973). Because of the cross-reactivity of 4-amino-N10-methyl pteroic acid in the MTX RIA of urine, samples collected more than 24 h after a single dose of MTX, or at any time during long-term MTX treatment, will give falsely high results for urinary MTX excretion.…”
Section: Antiserum Productionmentioning
confidence: 99%
“…The great improvement in antitumour therapy achieved with it in recent years has resulted not only from increased clinical experience, but also from a knowledge of the pharmacokinetics of the drug (Henderson et al, 1965a;Henderson, Adamson and Oliverio, 1965b;Huffman et al, 1973;Bischoff et al, 1971;Dedrick, Bischoff and Zaharteo, 1970). The value of measuring the concentration of MTX in various body fluids during treatment has recently been shown by a number of workers (Bleyer, Chabner, and Ommaya, 1973;Freeman-Narrod et al, 1975;Frei et al, 1975;Shapiro, Young and Mehla, 1975).…”
mentioning
confidence: 99%